MiR-20a is upregulated in serum from domestic feline with PKD1 mutation - Scalon, Marcela Corrêa (2022)
Polycystic kidney disease (PKD), also known as autosomal dominant polycystic kidney disease (ADPKD) is a genetically heterogeneous condition characterized by cysts in renal parenchyma. It is the most prevalent inherited disease of domestic cats. MicroRNAs (miRNAs or ncRNA) are short, noncoding, single-stranded RNAs that may induce PKD cytogenesis by affecting numerous targets genes as well as by directly regulating PKD gene expression. We compared the relative expression profile of miR-20a, -192, -365, -15b-5p, and -16-5p from plasma and serum samples of nine domestic cats with PKD1 mutation, detected by polymerase chain reaction (PCR), and a control group (n = 10). Blood samples from cats with PKD1 mutation provide similar concentrations of microRNAs either from plasma or serum. Serum miR-20a is upregulated in PKD group with p < 0.005; Roc curve analysis showed an AUC of 90,1% with a cut-off value sensitivity of 77.8% and specificity of 100%. This data provides important information regarding renal miRNA expression in peripheral blood sampling.